QRIS DAN PENGARUHNYA TERHADAP IMPULSIVE BUYING PADA MASYARAKAT KOTA MEDAN - Lubis, Kartika Sari; Winata, Edi; Sulaiman, Fahmi (Smart Education, 2025)
Abstract: Quick Response Indonesia Standard (QRIS) is one of the payment methods used by server-based electronic money applications, electronic wallets or mobile banking and has the potential to expand the acceptance of national non-cash payments more efficiently. The growing innovation towards digital payment has in fact changed people's lifestyles, especially in Medan city, which has led to impulsive buying behaviour, which is an irrational purchase and is associated with a quick and unplanned purchase, followed by a conflict of thoughts and emotional impulses. About 41% of Generation Z customers are impulsive shoppers, followed by 34% of Millennials and 32% of Generation Xers. The urgency of this research is to analyse the behavioural model of using the QRIS application as an effort to avoid impulsive buying. Based on the PwC (Pricewaterhouse Coppers) survey related to Global Consumer Insight, it illustrates how the digital payment system is turning into a trend or what is commonly called a cashless society. The survey results noted that 47% of respondents in Indonesia currently use digital payments. The purpose of this study is to avoid impulsive buying for QRIS users with the Unified Theory of Acceptance and Use of Technology (UTAUT) model in the context of information technology acceptance which integrates the technology acceptance domain into one user behaviour as the main dependent variable. This research method combines quantitative and qualitative analysis (mix method) conducted in Medan City with the object of research is QRIS users in making offline transactions who make transactions at Coffeeshop which is visited by Generation Z, namely Starbucks, Zircon Chill Coffee Shop, Doppio Coffee Shop, Palms Medan Coffee Shop, Mano Indonesia, Lorong Coffeeshop, FORE, and Hardapana Cffeeshop) and Fashion Stores at Sun Plaza and Deli Park Mall and the help of Structural Equation Model Partial Least Square (SEM PLS) as the method used to see behavioural relationships. The results of the study state that QRIS affects impulsive buying in people in Medan city. The testing of hypotheses to research this proves that the performance of expectancy or expectations of them were found significant performance intention or intention users behavior.This means performanace expectancy affect behavior intention that the use of the digital qris very fast and efficient. Keywords: QRIS, Impulsive Buying, Mobil Banking, Cashless society, global consumer insight. Abstrak: Quick Response Indonesia Standard (QRIS) merupakan salah satu metode pembayaran yang digunakan oleh aplikasi uang elektronik berbasis server, dompet elektronik atau mobile banking dan berpotensi memperluas penerimaan pembayaran nontunai nasional secara lebih efisien. Inovasi yang berkembang terhadap digital payment faktanya merubah gaya hidup masyarakat khususnya di kota Medan yang menimbulkan perilaku impulsive buying yaitu pembelian tidak rasional dan diasosiasikan dengan pembelian yang cepat dan tidak direncanakan, diikuti oleh adanya konflik fikiran dan dorongan emosional. Sekitar 41% pelanggan Generasi Z adalah pembelanja impulsive, diikuti oleh 34% generasi Milenial dan 32% Generasi X. Urgensi penelitian ini adalah untuk melakukan analisis model perilaku penggunaan aplikasi QRIS sebagai upaya untuk menghindari impulsive buying. Berdasarkan survei PwC (Pricewaterhouse Coppers) berkaitan dengan Global Consumer Insight memberikan gambaran betapa sistem pembayaran digital berubah menjadi tren atau yang biasa disebut dengan cashless society. Hasil survey mencatat 47% responden di Indonesia saat ini menggunakan digital payment. Tujuan penelitian ini untuk menghindari impulsive buying bagi pengguna QRIS dengan model Model Unified Theory of Acceptance and Use of Technology (UTAUT) dalam konteks penerimaan teknologi informasi yang mengintegrasikan domain penerimaan teknologi ke dalam satu perilaku pengguna sebagai variabel dependen utama. Metode penelitian ini menggabungan analisis kuantitatif dan kualitatif (mix method) yang dilakukan di Kota Medan dengan objek penelitian adalah pengguna QRIS dalam melakukan transaksi offline yang melakukan transaksi di Coffeeshopyang banyak didatangi oleh Generasi Z yaitu Starbucks, Zircon Chill Coffee Shop, Doppio Coffee Shop, Palms Medan Coffee Shop, Mano Indonesia, Lorong Coffeeshop, FORE, dan Hardapana Cffeeshop) serta Fashion Store di Sun Plaza dan Deli Park Mall dan bantuan Structural Equation Model Partial Least Square (SEM PLS) sebagai metode yang digunakan untuk melihat hubungan perilaku Pengujian hipotesis pada penelitian ini membuktikan bahwa performance expectancy atau ekspektasi kinerja berpengaruh signifikan postif terhadap behavior intention atau niat pengguna. Hal ini berarti performanace expectancy mempengaruhi behavior intention bahwapenggunaan pembayaran digital QRIS sangat cepat dan efisien. Kata kunci: QRIS, Pembelian Impulsiive, Mobile Banking, Uang Tunai, Masyarakat, Global